2016
DOI: 10.2196/humanfactors.5177
|View full text |Cite
|
Sign up to set email alerts
|

The Usability of Diabetes MAP: A Web-delivered Intervention for Improving Medication Adherence

Abstract: BackgroundWeb-delivered interventions are a feasible approach to health promotion. However, if a website is poorly designed, difficult to navigate, and has technical bugs, it will not be used as intended. Usability testing prior to evaluating a website’s benefits can identify barriers to user engagement and maximize future use.ObjectiveWe developed a Web-delivered intervention called Diabetes Medication Adherence Promotion (Diabetes MAP) and used a mixed-methods approach to test its usability prior to evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Although some usability studies employ a large number of participants, this is mostly done to provide sufficient sample size for quantitative analyses, and additional participants yield relatively few new usability concerns [ 40 - 42 ]. In addition, our usability findings build upon other recent studies of patient-facing diabetes health apps [ 50 , 53 , 59 ]. Georgsson et al used a similar mixed-methods approach to evaluate the usability of their mHealth system for diabetes type 2 self-management [ 53 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Although some usability studies employ a large number of participants, this is mostly done to provide sufficient sample size for quantitative analyses, and additional participants yield relatively few new usability concerns [ 40 - 42 ]. In addition, our usability findings build upon other recent studies of patient-facing diabetes health apps [ 50 , 53 , 59 ]. Georgsson et al used a similar mixed-methods approach to evaluate the usability of their mHealth system for diabetes type 2 self-management [ 53 ].…”
Section: Discussionsupporting
confidence: 75%
“…Several prior studies have reported the design and usability of patient-facing health apps and Web-based interventions for patients with diabetes [ 50 , 53 - 58 ]. Approaches to the design of these health apps and Web-based interventions typically employ some variation of user-centered design [ 56 - 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If working with a low-income population, for example, adopting a low-cost technology (e.g., basic cell phone technology: text messaging and voice communications) and/or providing a stipend to cover costs may improve engagement [20]. Additionally, conducting usability studies can help identify and address technical issues that may discourage engagement in a longer trial [44]. …”
Section: Discussionmentioning
confidence: 99%
“…The review concluded that further research is necessary to improve the design, content, and features from a patient perspective [ 25 ]. To date, only a few studies [ 14 , 26 , 27 ] have reported user requirements regarding the design and development of patient-centered HIT to support T2DM patients in self-managing their medications [ 28 ]. Requirements reported in these studies included reliable information on medication side effects and interactions, electronic messaging, selectively disclosing information, refill reminder functionality, and a user-friendly format [ 14 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%